A new species of Polyipnus (Teleostei: Stomiiformes) from the western Pacific, with comments on the P. triphanos species complex - Harold, Antony S.; Kemp, Iris M.; Shore, Sarah K. (Zootaxa, 2016)
A new species of the teleostean family Sternoptychidae, Polyipnus notatus n. sp., is described based on material collected mainly off Taiwan in the South China Sea. The new species is most similar to P. triphanos, based on the presence of a single posttemporal spine, lack of scale spination, and the second and third ACA (=supra-anal) photophores elevated relative to the first and connected to each other in a common organ. These characters typify other members of the P. asteroides species group that occur in various tropical to temperate ocean basins. Based on a limited sample of 27 specimens, P. notatus (maximum observed size 30.7 mm SL) appears to be smaller than most other congeners. It is also characterized by an unusual lateral pigment bar, which is narrow and distinctly triangular. Based on the material examined, the geographical distribution of the species appears to be restricted to the South China Sea and adjacent minor ocean basins.